Vitamin D deficiency and impaired placental function: potential regulation by glucocorticoids?. Issue 5 (May 2017) - Yates, Nathanael; Crew, Rachael C; Wyrwoll, Caitlin S
Abstract : Maternal vitamin D deficiency has been implicated in a range of pregnancy complications including preeclampsia, preterm birth and intrauterine growth restriction. Some of these adverse outcomes arise from alterations in placental function. Indeed, vitamin D appears critical for implantation, inflammation, immune function and angiogenesis in the placenta. Despite these associations, absence of the placental vitamin D receptor in mice provokes little effect. Thus, interactions between maternal and fetal compartments are likely crucial for instigating adverse placental changes. Indeed, maternal vitamin D deficiency elicits changes in glucocorticoid-related parameters in pregnancy, which increase placental and fetal glucocorticoid exposure. As in utero glucocorticoid excess has a well-established role in eliciting placental dysfunction and fetal growth restriction, this review proposes that glucocorticoids are an important consideration when understanding the impact of vitamin D deficiency on placental function and fetal development.